Comportamentos de indisciplina: um estudo com a 4a. série do ensino fundamental - Yasumaru, Vital Toshio (2006)
As regards to the problems faced by the teachers, misbehavior in classroom is today one of the most boarded subjects. Although it is considerable the amount of works of reflection on the subject, is scarce the number of empirical research that aims to study this phenomenon as it occurs in the classroom. This research, which has as main purpose the understanding of the occurrence of misbehaviors in classroom, aims to comprehend why they occur, identifying the more recurrent ones, the antecedent situations and how teachers act ahead of these behaviors. We work with teachers and students of five classes at Basic Education of two public schools at São Paulo. In the data collection, we made use of the observation in classroom, with cursive register of the occurrence. Our analysis of data is based on the Functional Analysis of the teachers and students interaction. Therefore, the relations between the behaviors of indiscipline with its antecedents and consequences were identified. It was verified that student s most recurrent behavior, in all the groups, was talking and walking in classroom. The occurrence of violent or aggressive behaviors is practically inexistent. Also was verified that teachers propose small quantity of lessons in a long period of time, lessons which showed up repetitive (copy-exercise-correction at the blackboard) and that didn t demand students active involvement. Such situations promote the misbehavior occurrence. It was noticed that two of the teachers excessively demand the silence of the students in classroom, while the other three had revealed more permissive. All of them, however, had presented a coercitive intervention model, what is not effective at misbehavior decrease or elimination. The occurrence of misbehaviors is related to the didactic-pedagogical performance of the teachers. If the teachers do not demand suitable activities in order to keep the students engaged in academic activities to the available time, misbehaviors occur. Nevertheless, the teachers need act in function of the student learning instead of being acting constantly in function of discipline maintenance in classroom